2022
DOI: 10.3390/ma15217520
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Switching Characteristics of Alloyed AlSiOx Insulator for Neuromorphic Devices

Abstract: Charge-based memories, such as NAND flash and dynamic random-access memory (DRAM), have reached scaling limits and various next-generation memories are being studied to overcome their issues. Resistive random-access memory (RRAM) has advantages in structural scalability and long retention characteristics, and thus has been studied as a next-generation memory application and neuromorphic system area. In this paper, AlSiOx, which was used as an alloyed insulator, was used to secure stable switching. We demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Kim et al [ 36 ] examined the RS characteristics in an alloy memory system based on HfTiO x . Lee et al [ 37 ] demonstrated fundamental RS properties and achieved multilevel switching behavior by applying the DC sweep and pulses. Wang et al [ 38 ] obtained analog switching behavior and synaptic function by interface-engineering in HfO 2 -based RRAM through O 3 pulse treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [ 36 ] examined the RS characteristics in an alloy memory system based on HfTiO x . Lee et al [ 37 ] demonstrated fundamental RS properties and achieved multilevel switching behavior by applying the DC sweep and pulses. Wang et al [ 38 ] obtained analog switching behavior and synaptic function by interface-engineering in HfO 2 -based RRAM through O 3 pulse treatment.…”
Section: Introductionmentioning
confidence: 99%